Grandmother's Role as a Personal Reference toward Exclusive Breastfeeding Behavior - Nurul Pujiastuti (Media Karya Kesehatan, 2021)
Grandmother's role in the behavior of exclusive breastfeeding is very necessary because the grandmother is the closest person in the family. Its existence influences decision-making in various family matters, especially the care of children from birth to adulthood. This study aims to analyze differences in the role of grandmothers as a personal reference for exclusive breastfeeding behavior. This type of experimental Quasy research was conducted in May-July 2018 in Sidoarjo Regency, East Java, Indonesia by dividing two experimental groups, namely the treatment group and the control group. Both groups started with a pre-test, and after the treatment was measured again (post-test). Statistical analysis used multivariate covariance analysis (MANCOVA) to test whether there were differences in treatment between the control group and the treatment group after adjusting for confounding variables, namely formula milk promotion. The results of the pre-test statistical test showed that the value of p = 0.384 means that there is no difference in the role of the grandmother on the exclusive breastfeeding behavior of the control group and the treatment group. The results of the post-test statistical test showed that the value of p = 0.000 means that there are differences in the role of the grandmother on the exclusive breastfeeding behavior of the control group and the treatment group. The role of the grandmother as a personal reference can influence exclusive breastfeeding behavior so that it can be a form of family support for the mother for exclusive breastfeeding and can be used as a way to support exclusive breastfeeding mothers. Keywords: Behavior, exclusive breastfeeding, grandmother’s role, personal reference.